The Long-Run Effects of Tradeon Income and Income Growth - Brunner, Allan (IMF Working Papers; Working Paper, 2003)
This paper examines the dynamic relationship between trade and income. While most economists agree that increased trade leads to an increase in average income, economic theory is ambiguous about the possible effects on the long-run growth rate of the economy. Using a dynamic panel data model, the hypotheses of no long-run effects of trade on income and on income growth are tested explicitly. The possibility of endogeneity is addressed by constructing an instrument for trade by extending Frankel and Romer's (1999) cross-sectional approach to the case of a panel data model. The empirical results indicate that trade has a large and significant effect on the level of income, but the effect on income growth is small and non-robust to model specification.